The Routledge handbook of Soviet and Russian military studies
1 online resource
Keywords: "This handbook brings together historical and contemporary essays about Soviet and Russian military studies, to offer a comprehensive volume on the topic. Comprising essays written by acknowledged specialists, the handbook examines the development of the Russian and Soviet armed forces from the Napoleonic Wars all the way through to the course and conduct of the 'Special Military Operation' in Ukraine. Divided into thematic and chronological sections, the volume looks at wars fought by the Tsarist regime through to the First World War; the Soviet Union's 'Great Patriotic War', from 1941-45; the Cold War (including the Soviet war in Afghanistan); and Russia's post-Soviet wars and military development. In addition, the volume also includes a section that analyses a number of 'overarching themes', including the development of Russian and Soviet airpower, partisan warfare, counterinsurgency and the role of women in Russian and Soviet armed forces. The volume concludes with an essay looking at whether, using the historical material and material on the conduct of the war in Ukraine, we can reasonably talk of a 'Russian way of war'. This volume will be of considerable interest to students of the Soviet Union and Russia, strategic studies and military history"--